Optimizing Generative Design for Cam Curve Through NURBS Approach based on Objective Constraint - Li Linwen; Lu Bo; Xiao Yang; Zhao Zhe (Jixie chuandong)
A general searching method is presented for the optimum generative design of a cam curve.This method involves the use of Non Uniform Rational B- Splines（ NURBS） outputs for representing the follower motions,namely as displacement,velocity and acceleration. Using a numerical iterative approach optimized in a constraint and objective function set,the optimum design is obtained by simultaneously adjusting the multiple control points and weights of the NURBS parameters. The results yield to a generative motion that satisfy the prescribed terminal conditions that include performance criteria related to kinematic,geometry,pressure angle as well as undercutting property of the system. Particularly,this method can control not only the level but also the local shape of the motion curves to better performance property. The effectiveness of the approach is illustrated by comparing the results between the present method and the conventional curves for a disk cam- follower mechanism specified in Dwell- Rise- Dwell（ DRD） follower motion type. Example shows that the obtained cam profile provide a good solution for the strong coupling constraints in the cam optimization design.